Massekhet Gittin chapters 4-5: text, translation, and commentary - Yiśreʾeli, ʿAnat (A feminist commentary on the Babylonian Talmud, 2024)
Anat Israeli and Tal Ilan present a feminist commentary on chapters 4 and 5 of Tractate Gittin in the order of Nashim in the Mishnah. While in the Babylonian Talmud a large unity is devoted to the conquest of Jerusalem and the destruction of the Temple, the present commentary focuses on women's roles in this war